Fusing Emotion and Art Communication: A Disc Interval-Valued Fermatean Fuzzy Decision-Making Approach - Liu Peng (IEEE Access)
In clinical therapy, enhancing emotional engagement and experience is held to be pivotal for achieving better treatment outcomes. The traditional application techniques of integrating emotional feedback with interventions are often imprecise in capturing real-time variations in emotions and translating these into effective decision-making processes. This paper bridges this gap by proposing an innovative Disc Interval-Valued Fermatean Fuzzy structure to be presented in order to improve the accuracy of the process of decision-making while dealing with some imprecise emotional data. We propose some basic aggregation operation techniques based on Ordered Weighted Averaging and Ordered Weighted Geometric, which are able to capture real-time emotions. The operations used are applied to a case study of interactive digital art that is meant to enrich clients’ emotional experiences and overall effectiveness of clinical therapy. Then, the new format is compared with the technique of CoCoSo that presents an improved flexibility and accuracy hence producing better therapy results.